Reporting Experiments in Homeopathic Basic Research—Description of the Checklist Development. (10th March 2011) - Stock-Schröer, B.; Albrecht, H.; Betti, L.; Dobos, G.; Endler, C.; Linde, K.; Lüdtke, R.; Musial, F.; van Wijk, R.; Witt, C.; Baumgartner, S.
Abstract : The objective of this study was to develop a criteria catalogue serving as a guideline for authors to improve quality of reporting experiments in basic research in homeopathy. A Delphi Process was initiated including three rounds of adjusting and phrasing plus two consensus conferences. European researchers who published experimental work within the last 5 years were involved. A checklist for authors provide a catalogue with 23 criteria. The "Introduction" should focus on underlying hypotheses, the homeopathic principle investigated and state if experiments are exploratory or confirmatory. "Materials and methods" should comprise information on object of investigation, experimental setup, parameters, intervention and statistical methods. A more detailed description on the homeopathic substances, for example, manufacture, dilution method, starting point of dilution is required. A further result of the Delphi process is to raise scientists' awareness of reporting blinding, allocation, replication, quality control and system performance controls. The part "Results" should provide the exact number of treated units per setting which were included in each analysis and state missing samples and drop outs. Results presented in tables and figures are as important as appropriate measures of effect size, uncertainty and probability. "Discussion" in a report should depict more than a general interpretation of results in the context of current evidence but also limitations and an appraisal of aptitude for the chosen experimental model. Authors of homeopathic basic research publications are encouraged to apply our checklist when preparing their manuscripts. Feedback is encouraged on applicability, strength and limitations of the list to enable future revisions.